Socioeconomic Status as a Determinant of Diabetes Mellitus Incidence at Ujungloe Public Health Center - Ainul Jariah; Hamdana; Nurlaela Amin (Diagnosa, 2026)
Background: Diabetes mellitus is a non-communicable disease with a continuously rising global and national prevalence, and its occurrence is influenced not only by biological factors but also by social determinants such as socioeconomic status, including education, occupation, and income. Purpose: This study aimed to determine the relationship between socioeconomic status and the incidence of diabetes mellitus at Ujungloe Public Health Center. Methods: This quantitative study used an analytical observational approach with a cross-sectional design. The population consisted of 912 patients with diabetes mellitus, from whom 90 respondents were selected using purposive sampling. Data were collected through questionnaires and medical records and analyzed using Spearman's rank correlation test with a significance level of p < 0.05. Results: The results showed a significant relationship between socioeconomic status and the incidence of diabetes mellitus, with p = 0.000 (p < 0.05) and a correlation coefficient of r = 0.809, indicating a very strong positive relationship. Respondents with low socioeconomic status tended to have higher blood glucose levels than those in the middle and high categories. Conclusion: Socioeconomic status is an important determinant of diabetes mellitus incidence through its influence on lifestyle, healthcare access, and health literacy.